2003
DOI: 10.1002/marc.200390031
|View full text |Cite
|
Sign up to set email alerts
|

Ultimately Specific 1,4‐cis Polymerization of 1,3‐Butadiene with a Novel Gadolinium Catalyst

Abstract: Novel complexes [(C5Me5)2Ln][B(C6F5)4] (Ln = Pr, Nd, or Gd) were prepared, which in combination with iBu3Al efficiently induce highly 1,4‐cis‐specific polymerization of butadiene. The activity of the Gd complex/iBu3Al system is high enough to exhibit good catalytic activity even at low temperature. Polymerization at −78 °C gave polybutadiene with nearly perfect 1,4‐cis microstructure (>99.9%) with sharp molecular weight distribution (Mw/Mn = 1.45) and in reasonable yield. ORTEP drawing of 2b. Selected bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 15 publications
3
59
0
1
Order By: Relevance
“…[86] Further evidence that cationic hydrocarbyl complexes act as the active species is given by the following observation: The activation of the cationic bis(pentamethylcyclopentadienyl) complexes [LnCp* 2 ][B(C 6 F 5 ) 4 ] (Ln ¼ Pr, Nd, Sm) with Al(i-Bu) 3 was reported to afford highly cis-1,4 selective initiators for 1,3-butadiene polymerization (Table 7). [12,83,87] The above findings may also imply that, in the case of the industrially applied multicomponent catalysts typically consisting of lanthanide carboxylate, aluminum alkyl and Lewis acid, discrete cationic alkyl species may be formed in situ or exist in equilibrium with non-ionic compounds (Scheme 14). [88,89] …”
Section: Polymerization Of Ethylene and A-olefinsmentioning
confidence: 98%
“…[86] Further evidence that cationic hydrocarbyl complexes act as the active species is given by the following observation: The activation of the cationic bis(pentamethylcyclopentadienyl) complexes [LnCp* 2 ][B(C 6 F 5 ) 4 ] (Ln ¼ Pr, Nd, Sm) with Al(i-Bu) 3 was reported to afford highly cis-1,4 selective initiators for 1,3-butadiene polymerization (Table 7). [12,83,87] The above findings may also imply that, in the case of the industrially applied multicomponent catalysts typically consisting of lanthanide carboxylate, aluminum alkyl and Lewis acid, discrete cationic alkyl species may be formed in situ or exist in equilibrium with non-ionic compounds (Scheme 14). [88,89] …”
Section: Polymerization Of Ethylene and A-olefinsmentioning
confidence: 98%
“…The 1 H-NMR spectra of all BR sample (Fig. 2a) showed the signals at a chemical shift (d) of 4.8-5.2 ppm for @CH 2 of vinyl21,2 configurations and 5.2-5.8 ppm for -CH@ of 1,4-butadiene and 1,2-butadiene units [11]. It was found that the Nd-BR and Co/Nd-BR exhibited lower signals for @CH 2 of vinyl21,2 structure than Co-BR.…”
Section: Resultsmentioning
confidence: 98%
“…[17] In addition, the reported activation sequence of the Cp* 2 Gd + fragment by triisobutylaluminum (TIBA) suggests that polymer chains may be initiated by aluminum-bound isobutyl groups.Finally,the carbazole substituent in 1c is UV/ Vis-active and fluorescent, and will result in UV/Vis-active polymers,ifincorporated. [17] In addition, the reported activation sequence of the Cp* 2 Gd + fragment by triisobutylaluminum (TIBA) suggests that polymer chains may be initiated by aluminum-bound isobutyl groups.Finally,the carbazole substituent in 1c is UV/ Vis-active and fluorescent, and will result in UV/Vis-active polymers,ifincorporated.…”
Section: Resultsmentioning
confidence: 99%